TaniMarket: An E-Commerce Platform for Empowering Local Agricultural MSMEs - Nababan, Adli Abdillah; Miftahul Jannah; Medhian Ahmadi Putra; Jijon Raphita Sagala; Harefa, Ade May Luky (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The development of information technology provides a great opportunity for Micro, Small, and Medium Enterprises (MSMEs) to market their products digitally, including in the agricultural sector. However, there are still many agricultural MSME actors who have not utilized this technology optimally. This research aims to build a webbased information system called TaniMarket, which can be used as a means of marketing agricultural products by MSME actors. Application development is carried out using the Waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The application is built using PHP programming language version 8.1, the CodeIgniter 4 framework, and the MySQL database. This system consists of two main roles, namely admin and user. Admins have full access to product and category management features, including adding, modifying, and deleting data, as well as uploading images and order information. Meanwhile, users can view a list of products by category and place orders directly through the WhatsApp button that has been provided with automatic messages. The results of the system test show that all features run according to the design that has been determined. The TaniMarket application is considered to be able to provide convenience for MSME actors in marketing their garden products more widely and efficiently. With a simple and responsive interface, this system also supports users in accessing product information quickly and practically. Overall, this application is an effective digital solution in supporting the increase in the competitiveness of agricultural MSMEs in the era of digital transformation.